Edukasi dan Pemeriksaan Kesehatan Jiwa Remaja Menggunakan Instrumen IDASS-Y di SMPN 23 Padang - Bunga Permata Wenny; Mahathir Mahathir; Atih Rahayu Ningsih; Windy Freska; Devia Putri Lenggogeni; Rika Sarfika; Randy Refnandes; Agus Sribanowo; Sovia Susianty; Siti Yuliharni (Warta Pengabdian Andalas, 2023)
Adolescents are exposed to a variety of stressors during the challenging adolescent transition phase. Nowadays, adolescents are more susceptible to mental health issues, which are reportedly becoming more prevalent globally. Involve schools in initiatives to address adolescent mental health to raise teenage understanding and awareness. Adolescents' mental health status can be assessed by mental health screening and education, and mental health education can help them know more about their mental health. This activity aims to expand students' awareness of mental health issues at public junior high schools in Padang. The IDASS-Y adolescent health self-reporting instrument was used to implement the intervention. The dissemination of information about adolescents' mental health issues and strategies for preventing them served as the basis for educational initiatives. According to the activity's findings, 25 students in Junior High School had mild depression (92.6%), one who had moderate depression (3.7%), and one who had severe depression (3.7%). The prevalence of anxiety among SMPN 23 students was 25 mildly anxious individuals (92.6%) and two moderately anxious individuals (7.4%). Twenty participants (74.1%) reported light stress, six (22.2%) reported moderate stress, and one (3.7%) reported severe stress. The knowledge score has improved before and during mental health education—the importance of involving schools in mental health management, including education and screening.